2021
DOI: 10.1002/mus.27184
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes and experience of pregnancy in limb girdle muscular dystrophy type R9

Abstract: Introduction: Published information about the experiences of pregnancy in limb girdle muscular dystrophy (LGMD) is limited and does not specify LGMD type, limiting utility. We describe the experience and outcomes of pregnancy in a cohort of women with LGMD type R9 (LGMDR.Methods: All women 18 y of age or older with a genetic and clinical diagnosis ofLGMDR9 who are enrolled in the University of Iowa Wellstone dystroglycanopathy natural history study (clinicaltrials.gov NCT00313677) were invited to complete a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Awater et al 1 showed significant heterogeneity of experiences and outcomes during pregnancy, delivery, and through the postpartum period in patients with hereditary neuromuscular disorders. Similar to the present study, 7 a persistent worsening of weakness in over half the women with LGMD, in approximately a third with Charcot–Marie Tooth disease and in only 12% with facioscapulohumeral dystrophy (FSHD) was noted 1 . Women with myotonic dystrophy type 1 (DM1) did not report an exacerbation of weakness during pregnancy in this study, but in a large registry study by Johnson and colleagues, women reported significant worsening of mobility, pain, and ability to perform activities during pregnancy compared to 6 mo pre‐pregnancy that did not improve in the 6 mo following pregnancy 1,2 .…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Awater et al 1 showed significant heterogeneity of experiences and outcomes during pregnancy, delivery, and through the postpartum period in patients with hereditary neuromuscular disorders. Similar to the present study, 7 a persistent worsening of weakness in over half the women with LGMD, in approximately a third with Charcot–Marie Tooth disease and in only 12% with facioscapulohumeral dystrophy (FSHD) was noted 1 . Women with myotonic dystrophy type 1 (DM1) did not report an exacerbation of weakness during pregnancy in this study, but in a large registry study by Johnson and colleagues, women reported significant worsening of mobility, pain, and ability to perform activities during pregnancy compared to 6 mo pre‐pregnancy that did not improve in the 6 mo following pregnancy 1,2 .…”
supporting
confidence: 92%
“…4 In this issue of Muscle & Nerve, Libell et al report on the experiences and outcomes of pregnancy in a focused subset of women with limb girdle muscular dystrophy (LGMD) R9. 7 Normal physiological changes in pregnancy place significant strains on several body systems, many of which may already be challenged in those with neuromuscular disorders. Hematologically, there are dilutional anemia, reduced plasma protein levels and a pro-thrombotic state.…”
mentioning
confidence: 99%
See 3 more Smart Citations